Estudo de tendência da resistência antimicrobiana e sua associação imediata e tardia com o consumo de antimicrobianos, de 2007 a 2016, em um hospital de ensino de grande porte em São Paulo, Brasil - Federico, Marilia Pinto [UNIFESP] (2018)
Objectives: To evaluate the trend of antimicrobial consumption and bacterial resistance and to verify the immediate and late association between these variables. Methods: An ecological study was carried out in a large teaching hospital in São Paulo from 2007 to 2016. Consumption and resistance data were collected from the reports of the supply sector and the institution's central laboratory, respectively. Positive culture data from clinical samples of blood, urine and respiratory secretions from adult patients hospitalized during the study period were analyzed. Consumption was calculated in daily dose defined by 100 patients per day (DDD/100pd), the trends were analyzed by the Mann-Kendal test and the association of consumption with resistance in the same year, one or two years later was investigated by linear regression of mixed effects. Results: The consumption of antimicrobials (113.4 DDD / 100pd) increased by 18.4% in the period studied and carbapenens, third-generation cephalosporins and glycopeptides were the most used antimicrobial classes in the hospital. A total of 22041 isolates were analyzed, most of them from the intensive care units and respiratory secretions and Klebsiella spp, coagulase negative Staphylococcus, P.aeruginosa, Acinetobacter spp, E.coli and S. aureus were the most common bacteria found. In ten years, the resistance of Klebsiella spp to carbapenens increased ≈4700.0% [1.4% (2/143) vs 67.0% (376/561); p = 0.0001], whereas meticillin-resistant S.aureus reduced 59.4% [68.6% (59/86) vs 30.2% (52/172); p = 0.007]. Positive (immediate) and negative (late) associations were most frequent in secondary relationships such as consumption of third generation cephalosporins with carbapenens resistant P. aeruginosa [β = 26.67%; IC95 (2.99; 50.35); p = 0.034] and of fluoroquinolones with methicillin-resistant S. aureus [β = -3.93; IC 95 (-6.90; -0.96); p = 0.034], in that order. Conclusion: A worrisome situation was revealed by the excessive consumption of antimicrobials and the growth of the occurrence of Gram-negative bacteria. Negative associations were better explained by the restriction of the use of a antimicrobial favoring the increment of another and by the probable effectiveness of infection control measures.